Evaluation of the therapeutically approach of various types of periodontal disease. Part I: clinical aspects - Botero-B., Alejandro; Alvear-E., Fanny Stella; Vélez-L., María Eugenia; Botero-Z., Leticia; Velásquez-E., Hernando (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The study initiated with 69 patients, out of which 55 were available at the completion of the trial. Evaluations were made at the beginning, 3, 6, 12 and 24 months. The initial exam included the following socio demographic criteria: age, gender, tobacco use and family grouping. The clinical criteria included were: probing depth, clinical attachment, superficial bleeding, probing bleeding (Part I) and sub gingival micro flora. (Part II). Microbiological samples were taken from 6 different sites at the beginning. 12 and 18 months. The statistical analysis included the Chi square and Student’s T test for paired averages in time, both with a level of significance of 5%. Also a logistic regression analysis was done to find predictive variables of response to treatment. The objectives of this study (Part I) were: 1) to identify which of the social demographic variables, signs of periodontal disease and clinical parameters could anticipate a good or poor response to non-surgical traditional periodontal therapy (scaling and root planning per quadrant) 3 months after being applied. 2) to evaluate the behavior of clinical parameters after a 2 year follow-up period. Three months after treatment the changes (loss or gain) in clinical attachment (CA) allowed us to classify the patients as: Responsive (R) to 57 patients (82.6%) and Non Responsive (NR) to 12 (17.4%). The variables analyzed did not show individual or group association with the type of response to treatment, with the exception of supra gingival index plaque ≥ 2 (P = 0.05). Follow up after two years indicated that the alternative treatment (scaling and root planning complemented with systemic antibiotics) was beneficial for the NR that behaved during this period in the same way as the R, both showing stability in the CA.